Problemy genologii literackiej we współczesnej literaturze metodycznej = Problems of Literary Genology in Contemporary Methodical Literature - Bogołębska, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents elements of teaching of genology of methodical after-war literature in Secondary Schools. The test to define the objective, the place and importance of genological problems in school by means of curricula, text-books and methodical work is accompanied by the indication of substantial inexactnesses in this line. Some special problems in the field of assortment of contents during genological school-teaching are confronted with up-to-date methods of literary researches.
Keywords: genologia; literatura; metodologia